ECTOPARASITIC INFESTATION BY RHIPICEPHALUS SP. AND HETERODOXUS SPINIGER IN SHIH TZU DOGS - Iwan Ramdani; I Gede Soma; Sri Kayati Widyastuti (Buletin Veteriner Udayana, 2025)
Dogs are one of the most beloved pets kept by humans. Its relatively easy maintenance makes dogs so popular in all circles. Dogs have the potential to be a place for ectoparasites to live because they have soft and warm hair which is a favorable environment for ectoparasites. The purpose of this article is to find out how to diagnose, manage and treat cases of ectoparasite infestation in dogs. The case animal is a female dog weighing 5 kg in which the dog has skin problems with itching with a pruritus score of 7/10, an ulcer on the neck and alopecia on several parts of the body, on microscopic examination identified and found the presence of ectoparasites Heterodoxus sp. and Rhipicephalus sanguineus. The treatment used wormectin and diphenhydramine as causative treatment, and Chlorpheniramine maleate (CTM) and dexamethasone and amoxicillin as symptomatic. Two weeks of treatment showed good results, with the pruritus score decreasing to 3/10, and the ulcer caused by scratching closed completely, and the alopesia had grown hair although short. It is recommended that dogs be quarantined during treatment to prevent transmission, accompanied by bathing the dog twice a week and maintaining the cleanliness of the cage and environment to prevent the development of infectious agents.